Reflexiones en torno al estudio de los retablos portátiles peruanos y las cajas de imaginero del siglo XIX - Labán Salguero, Magaly Patricia (2020)
This article is an approximation to the study of peruvian portable altarpieces and “cajas de imagineros” of XIX century. This research propose a revision of diverse american denominations of altarpieces, pertinence of names such as: religious altarpiece, portable altarpiece, “capilla- retablo”, “demanda”, “caja de imaginero”, niche, triptych, “cajón sanmarkos” and “missa”. Analysing briefly historical backgrounds and standards of “cajas de imaginero” of XIX century. Presenting an state of the question and reflecting about concepts and theoretical influences of researchers, analysing their methodological and conceptual contributions. Considering the lack of chronological dating in those work of art pieces and workshop filiations, researcher’s methodological difficulties and their applied methods.